MafhÅ«m al-á¹£alawÄt â€˜inda majmÅ«â€˜at Joged Shalawat Mataram: DirÄsah fÄ« al-á¸¥adÄ«th al-á¸¥ayy - Suryadilaga, Muhammad Alfatih (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2014)
This study examines the spiritual dance tradition of Joged Shalawat Mataram (JSM), a spiritual dance originating from the Mataram Sultanate of Yogyakarta. The focus of this research study is to determine the meaning of á¹£alawah in the JSM community. The results of this study are as follows. Firstly, JSM is a socio-cultural phenomenon emanating out of religious traditions, classified as a spiritual dance or art of spiritual movements. Secondly, JSM is a phenomenon of â€˜livingâ€™ hadith. In this sense, the JSM tradition is based on hadith that reflect some basic principles of the Prophetâ€”those that command the reading of á¹£alawah to the Prophet and those that command the following of the Prophetâ€™s character. Thirdly, JSM is a phenomenon of symbols of religious culture. Fourthly, as a socio-religious movement JSM wants to convey the values of character education through Islamic art.DOI:Â 10.15408/sdi.v21i3.1220